WT-ANN based fault discrimination for transmission system - Venkata Lakshmi, P; N. S. Poojitha, P; Srinivasrao, Y (International Journal of Engineering and Technology, 2018)
Protection of transmission line is a complex in power system as the majority of the faults in power system are transmission faults. A proper protection is needed for transmission line for continuous power supply. To provide a strong as well as an efficient protection scheme, in this paper we are using wavelet technique and artificial neural network. By using these mentioned two techniques we can detect the faults in transmission line and also, we can classify the detected faults. Wavelet transform has strong mathematical, very fast and accurate tools for brief signal inside the transmission lines and synthetic neural network can make a unique between measured sign and associated signal that has different pattern.Â